Nuclear and Nucleolar Morphometric Changes in MGP Stained Oral Epithelial Cells In Cigarette Smokers and Non Smokers - Maria Shafiq, Ghazia Fatima, Zafar Iqbal, Faiz Ahmad Faiz, Qamir Aziz, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To compare nuclear and nucleolar morphometric changes in methyl green pyronin stained oral epithelial cells in cigarette smokers, passive smokers and non smokers Study design: A comparative cross sectional study Place and duration: Carried out in Postgraduate Medical Institute, Lahore. Duration was 6 months, March 2022 to August 2022. Methods: 120 subjects were equally divided into three main groups, cigarette smokers, passive smokers and non smokers, each fulfilling the inclusion and exclusion criteria. Buccal smears were collected by exfoliative cytology of mucosa and then stained by methyl green pyronin stain. The quantitative nuclear morphometric parameters i.e., nuclear and nucleolar diameter and area, and number of nucleoli, were measured. Results: Themedian of all nuclear parameters of smokers was significantly higher as compared to passive smokers and non-smokers in MGP stain (p ≤ 0.05). Further, effect of duration of smoking on morphometric variables showed significant (p< 0.05) results amongst the smokers in MGP stain. However, no significant differences were seen in all morphometric parameters with respect to frequency of cigarette smoking. Conclusion: The study confirms nuclear morphometric changes in oral epithelial cells of cigarette smokers indicating that smoking does influence cellular alterations. The simplicity of cytology technique with the use of methyl green pyronin stain is valuable screening tool for detecting early oral mucosal changes in high risk patients. Keywords: smoking, exfoliative cytology, nuclear morphometric parameters, methyl green pyronin stain.